Assessment Of Toxicity And Safety Margin Of Phenylalanine And Its Metabolites Through In-Vivo And In-Vitro Model (Journal of Pharmaceutical Negative Results, 2023)
Phenylalanine (PA), an emergent essential amino acid, is a building block of protein, which propagates significant metabolites to assure the compatibility of the body. During derangement of metabolism of PA or genetic mutation, which alters tyrosine synthesis, leads to phenylketonuria (PKU). Genetic similarities of Danio rario with humans allow the comparison of metabolic pathways in fish model.Objective:The study is to evaluate the toxicity and safety margin of Phenylalanine, and one of its metabolites, sodium phenylpyruvate (SPP). Toxicological assessment LC50 study (OECD TG 236), developmental toxicity study (total body length, head size, caudal fin length of embryo), and hepatoxicity study (SGPT, SGOT, Histopathology, i.e., sinusoidal dilation, cytolysis, karyolysis, cell-to-cell adhesion, vacuolization, and degenerated hepatocytes) has been performed on Danio rario model. For phenylalanine, LC50 values are, 1949, 829, 213, 133, 92.68 µg/ml, for phenylpyruvate, LC50 values are, 224.9, 169.82, 105.15, 97.05, 79.79 µg/ml. For developmental study, PA (0.5 mg/ml, 0.75mg/ml, 1mg/ml) and SPP (0.25mg/ml, 0.40mg/ml, 0.60mg/ml) concentrations are considered. For hepatotoxicity study on adult zebrafish groups (n=6), treated with PA and SPP with concentrations of 10mg/kg, 20mg/kg, and 40mg/kg separately.Results:After performing the experiment, it has been observed that for PA at its 1mg dose showed significant difference for head length/width and vertical/longitudinal caudal fin length. But for SPP, total body length and longitudinal caudal fin length showed significant different at 0.6 mg dose. The SGPT-SGOT test results for hepatotoxicity shows that SPP is more toxic than PA. Histopathological study of hepatocytes of Danio rario shows more positive results for SPP treatment than PA at dose dependent manner. Therefore, it can be concluded that a higher concetration of SPP can cause potential toxicity and health hazards.